IMPLEMENTATION OF AN INNOVATIVE LEARNING MODEL IN ELEMENTARY SCHOOLS IN BANDA ACEH - Side Efrida; Siti Mayang Sari; Akmaluddin; Jonni Sitorus (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Starting from the assumption that the educator-centered approach has many weaknesses. Meanwhile, the student-centered approach, the teacher's role is to help students find facts, concepts, or principles for themselves. Therefore, to refer to learning efforts towards building creative, interactive, innovative, and inspiring student character in the learning process in the classroom, it is necessary to implement innovative-based learning models. It is time for teachers to implement student-centered learning models as one of the learning innovations that make students the center of education. Innovative learning models are expected that students can develop their potential and abilities for the development of society, nation and state.